2003
DOI: 10.1037/0735-7044.117.6.1220
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Modifies Classical Conditioning of the Rabbit (Oryctolagus cuniculus) Nictitating Membrane Response.

Abstract: Cholesterol plays an important role in synapse formation, receptor function, and synaptic plasticity, and animal studies show that modifying cholesterol may improve learning and memory. Other data show that feeding animals cholesterol can induce beta amyloid accumulation. Rabbits (Oryctolagus cuniculus) fed 2% cholesterol for 8 weeks were given trace conditioning of the nictitating membrane response using a 100-ms tone, a 700-ms trace, and periorbital electrical stimulation or airpuff. Rabbits fed cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 106 publications
(215 reference statements)
8
43
0
Order By: Relevance
“…The slow rate and less than maximal levels of NMR conditioning in the current experiment are the result of these suboptimal NMR conditioning parameters (Kehoe & Macrae, 2002) as well as a complex procedure involving additional CS-alone (Habituation and test trials) and US-alone (Post Test 1) trials. In fact, when electrodermal stimulation was used as the US in the Schreurs et al (2003) study, there were also no differences in the rate or level of NMR conditioning between cholesterol-fed rabbits and controls. Nevertheless, cholesterol did seem to have facilitated NMR CRM in the present experiment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The slow rate and less than maximal levels of NMR conditioning in the current experiment are the result of these suboptimal NMR conditioning parameters (Kehoe & Macrae, 2002) as well as a complex procedure involving additional CS-alone (Habituation and test trials) and US-alone (Post Test 1) trials. In fact, when electrodermal stimulation was used as the US in the Schreurs et al (2003) study, there were also no differences in the rate or level of NMR conditioning between cholesterol-fed rabbits and controls. Nevertheless, cholesterol did seem to have facilitated NMR CRM in the present experiment.…”
Section: Discussionmentioning
confidence: 86%
“…Initial studies examining the ability of cholesterol-fed rabbits to learn found that although a cholesterol diet elevated the number of beta amyloid labeled neurons, it actually improved classical conditioning of the nictitating membrane response (Schreurs, Smith-Bell, Lochhead, & Sparks, 2003). It was only when cholesterol-fed rabbits displayed beta amyloid plaque-like structures induced by adding copper to the drinking water that classical conditioning of the nictitating membrane response (NMR) was retarded .…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Controversial results have also been obtained in animal studies [22,23] . Most observational studies were cross-sectional, the few longitudinal studies mostly examined manifest dementia but not MCI as the endpoint.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have examined the association of plasma lipid levels to cognitive function, and they reported inconsistent results (5,7,(42)(43)(44). Results in animal studies (45,46), and studies relating plasma lipid lowering treatment to cognitive functioning (7,12,43,47,48) have also been conflicting. Most observational studies were cross-sectional (9,43,(49)(50)(51), and some of the few longitudinal studies included individuals with QD or AD and did not provide methods to limit inclusion of such individuals (52).…”
Section: Discussionmentioning
confidence: 99%